2021
DOI: 10.3390/polym13162645
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Thermoplastic Polyamide Elastomers Based on Amorphous Polyetheramine with Damping Performance

Abstract: Novel thermoplastic polyamide elastomers (TPAEs) consisting of long-chain semicrystalline polyamide 1212 (PA1212) and amorphous polyetheramine were synthesized via one-pot melt polycondensation. The method provides accessible routes to prepare TPAEs with a high tolerance of compatibility between polyamide and polyether oligomers compared with the traditional two-step method. These TPAEs with 10 wt % to 76 wt % of soft content were obtained by reaction of dodecanedioic acid, 1,12-dodecanediamine, and poly(propy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This behavior seems to be associated not only with an increased free volume in polymers, but also with the presence of specific interactions of the CO 2 molecule with oxygen-containing phthalide and ketone groups. A similar phenomenon is often recorded when studying sorption and permeability in polymers containing ether groups (e.g., Pebax [69]).…”
Section: Experimental Gas Transport Propertiessupporting
confidence: 64%
“…This behavior seems to be associated not only with an increased free volume in polymers, but also with the presence of specific interactions of the CO 2 molecule with oxygen-containing phthalide and ketone groups. A similar phenomenon is often recorded when studying sorption and permeability in polymers containing ether groups (e.g., Pebax [69]).…”
Section: Experimental Gas Transport Propertiessupporting
confidence: 64%
“…It was observed that the storage modulus E ′ of TPAE-0 was much larger than that of HS-TPAEs, indicating that the incorporation of PTMG segments softened PA6 segments. 32 As a result, an elastic plateau at around room temperature with a low E ′ and minimal temperature dependency was observed. Notably, HS-TPAE-55 exhibits a smaller E ′ value than HS-TPAE-60 and HS-TPAE-70, despite having lower contents of soft segments.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, the peak at 𝛿 = 182.9 ppm (C k ) in the 13 C NMR spectrum suggests the presence of residual carboxyl groups in TPAE44. [29] This discrepancy arises from the co-evaporation of the PEA along with a large amount of water vapor during the prepolymerization. Therefore, it is necessary to maintain pressure to minimize PEA loss or consider increasing the ratio of PEA during feeding.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, studies have been conducted to prepare polyamide elastomers using PA1212 and PEA as the reaction segment. [28][29][30] Furthermore, TPAE products such as VES-TAMID E by Evonik Germany and UBESAT XPA by UBE Japan, also use PEAs and long-chain PA12 as constituents. Some studies have been devoted to the development of biobased polyamide elastomers.…”
Section: Introductionmentioning
confidence: 99%